Salvage treatment for children with relapsed/refractory germ cell tumors: The Associazione Italiana Ematologia Oncologia Pediatrica (AIEOP) experience. Issue 3 (18th December 2019) - De Pasquale, Maria Debora; D'Angelo, Paolo; Crocoli, Alessandro; Boldrini, Renata; Conte, Massimo; Bisogno, Gianni; Spreafico, Filippo; Inserra, Alessandro; Biasoni, Davide; Dall'Igna, Patrizia; Siracusa, Fortunato; Miele, Evelina; et al.
Abstract: Background: Malignant germ cell tumors (GCTs) are a heterogeneous group of rare neoplasms in children. Optimal outcome is achieved with multimodal therapies for patients with both localized and advanced disease, especially after the introduction of platinum‐based chemotherapy regimens. In this respect, data on salvage treatment for children with relapsed or platinum‐refractory disease are still limited. Methods: Retrospective analysis of data regarding patients affected by malignant GCTs with platinum‐refractory or relapsed disease after first‐line treatment according to AIEOP TCGM 2004 protocol was conducted. Results: Twenty‐one patients, 15 females and 6 males, were considered for the analysis. All 21 patients received second‐line conventional chemotherapy (SLCT), two of these immediately after surgery for local relapse removal. Two patients showed a progression of disease during SLCT and died of disease shortly thereafter, whereas 19 patients were in partial remission (PR) or complete remission (CR) after SLCT. Treatment after SLCT consisted in surgery on residual tumor mass (9/19) followed by high dose of chemotherapy (HDCT) with autologous hematopoietic stem cell support (16/19). The overall survival (OS) and event‐free survival of the whole populations are 71% and 66.6%, respectively. Platinum‐refractory patients OS is 54.5% compared with 91.5% of the relapsed group. There were no treatment‐related deaths. Conclusion: SLCT followed or not by HDCT is an effective salvage treatment for children with relapsed/refractory GCTs. However, the role of HDCT following SLCT needs to be further investigated, especially regarding the identification of specific patient subgroups, which can benefit from this more intensive treatment.